Aeropolitics in a post-COVID-19 world. (September 2020) - Macilree, John; Duval, David Timothy
Abstract: We review selected aeropolitical issues that may impact the international aviation sector post-COVID-19. Consideration regarding ICAO's role in coordinating safety provisions using existing frameworks will be important. Issues relating to national airline bailouts and recapitalisation as well as international ownership are also explored. We offer several further, as yet unanswerable, questions about future aeropolitical issues, including how ICAO will continue to address the crisis, implications for air services capacity restrictions, the impact of deglobalisation and the question of state aid for national carriers and other parts of the aviation system. Highlights: Aeropolitics is a critical part of the global aviation system. ICAO is playing a role in guiding pandemic-related aviation safety. Financial restructuring, including through government intervention, is happening. Other aeropolitical questions remain as yet unanswered.